Step
*
of Lemma
quadratic-formula1
∀a,b,c:ℝ.
  (a ≠ r0
  
⇒ (r0 ≤ ((b * b) - r(4) * a * c))
  
⇒ (∀x:ℝ. (((x = quadratic1(a;b;c)) ∨ (x = quadratic2(a;b;c))) 
⇒ (((a * x^2) + (b * x) + c) = r0))))
BY
{ (RepeatFor 5 ((D 0 THENA Auto))
   THEN (Assert r(2) * a ≠ r0 BY
               (RepeatFor 2 (ParallelOp 4) THEN nRMul ⌜r(2)⌝ 4⋅ THEN Auto))
   THEN Unfolds ``quadratic1 quadratic2`` 0
   THEN (GenConclTerm ⌜rsqrt((b * b) - r(4) * a * c)⌝⋅ THENA Auto)
   THEN (Assert (r0 ≤ v) ∧ ((v * v) = ((b * b) - r(4) * a * c)) BY
               (D -2 THEN Unhide THEN Auto))
   THEN D -1
   THEN Auto) }
1
1. a : ℝ
2. b : ℝ
3. c : ℝ
4. a ≠ r0
5. r0 ≤ ((b * b) - r(4) * a * c)
6. r(2) * a ≠ r0
7. v : {r:ℝ| (r0 ≤ r) ∧ ((r * r) = ((b * b) - r(4) * a * c))} 
8. rsqrt((b * b) - r(4) * a * c) = v ∈ {r:ℝ| (r0 ≤ r) ∧ ((r * r) = ((b * b) - r(4) * a * c))} 
9. r0 ≤ v
10. (v * v) = ((b * b) - r(4) * a * c)
11. x : ℝ
12. (x = (-(b) + v/r(2) * a)) ∨ (x = (-(b) - v/r(2) * a))
⊢ ((a * x^2) + (b * x) + c) = r0
Latex:
Latex:
\mforall{}a,b,c:\mBbbR{}.
    (a  \mneq{}  r0
    {}\mRightarrow{}  (r0  \mleq{}  ((b  *  b)  -  r(4)  *  a  *  c))
    {}\mRightarrow{}  (\mforall{}x:\mBbbR{}
                (((x  =  quadratic1(a;b;c))  \mvee{}  (x  =  quadratic2(a;b;c)))  {}\mRightarrow{}  (((a  *  x\^{}2)  +  (b  *  x)  +  c)  =  r0))))
By
Latex:
(RepeatFor  5  ((D  0  THENA  Auto))
  THEN  (Assert  r(2)  *  a  \mneq{}  r0  BY
                          (RepeatFor  2  (ParallelOp  4)  THEN  nRMul  \mkleeneopen{}r(2)\mkleeneclose{}  4\mcdot{}  THEN  Auto))
  THEN  Unfolds  ``quadratic1  quadratic2``  0
  THEN  (GenConclTerm  \mkleeneopen{}rsqrt((b  *  b)  -  r(4)  *  a  *  c)\mkleeneclose{}\mcdot{}  THENA  Auto)
  THEN  (Assert  (r0  \mleq{}  v)  \mwedge{}  ((v  *  v)  =  ((b  *  b)  -  r(4)  *  a  *  c))  BY
                          (D  -2  THEN  Unhide  THEN  Auto))
  THEN  D  -1
  THEN  Auto)
Home
Index